The world of the microscope - Oxlade, Chris; Stockley, Corinne; Chen, Kuo Kang (Tulsa, Okla. : EDC [distributor], 1989)
An introduction to the basic microscope as well as the electron microscope with colored illustrations, projects, and activities.
History of the microscope -- How to use a microscope -- Simple organisms -- Fungi -- Rocks and minerals -- Crystals -- Looking at insects -- Looking at plants.
A practical introduction with projects & activities--Cover.
Includes index and glossary.
6.7.
6.7
5-8
Keywords: Microscope and microscopy -- Juvenile literature; Microscope and microscopy; Microscopes